2012
DOI: 10.1039/c2cp40944e
|View full text |Cite
|
Sign up to set email alerts
|

Direct aqueous photochemistry of isoprene high-NOx secondary organic aerosol

Abstract: Secondary organic aerosol (SOA) generated from the high-NO(x) photooxidation of isoprene was dissolved in water and irradiated with λ > 290 nm radiation to simulate direct photolytic processing of organics in atmospheric water droplets. High-resolution mass spectrometry was used to characterize the composition at four time intervals (0, 1, 2, and 4 h). Photolysis resulted in the decomposition of high molecular weight (MW) oligomers, reducing the average length of organics by 2 carbon units. The average molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
68
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 112 publications
(137 reference statements)
9
68
3
Order By: Relevance
“…For example, Nguyen et al saw no evidence of photodegradation stopping after 0, 1, 2, 3, and 4 h of the aqueous photolysis of isoprene/NO x SOA. 19 Using actinometry to estimate the photon flux from the lamp used in experiments, we have concluded that 1 h of photolysis under our lamp is approximately equivalent to ∼4 h of photolysis under the overhead sun in the case of GUA/NO x SOA and ∼8 h in the case of APIN/O 3 SOA. The lifetime of droplets in cumulus clouds is typically in the range of 10−40 min, so the times probed here correspond to photolysis that may be experienced during several cloud cycles.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…For example, Nguyen et al saw no evidence of photodegradation stopping after 0, 1, 2, 3, and 4 h of the aqueous photolysis of isoprene/NO x SOA. 19 Using actinometry to estimate the photon flux from the lamp used in experiments, we have concluded that 1 h of photolysis under our lamp is approximately equivalent to ∼4 h of photolysis under the overhead sun in the case of GUA/NO x SOA and ∼8 h in the case of APIN/O 3 SOA. The lifetime of droplets in cumulus clouds is typically in the range of 10−40 min, so the times probed here correspond to photolysis that may be experienced during several cloud cycles.…”
Section: Resultsmentioning
confidence: 87%
“…The oxidants include ozone, which controls the oxidation of many unsaturated organics in clean air, and OH in the presence of NO x (=NO + NO 2 ) concentration, which is representative of an urban environment. In combination with previous studies of aqueous photolysis of limonene, isoprene, and naphthalene SOA, 15,19,20 this study provides a database for making general conclusions about the role of aqueous photochemistry in the atmospheric processing of SOA.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The reaction of aldehydes with OH radicals followed by the reaction with molecular oxygen yields peroxy acyl radicals (RC(O)OO; Finlayson-Pitts and Pitts, 2000). RC(O)OO can react with NO 2 to form PANs and react with HO 2 radicals to form RC(O)OOH (Finlayson-Pitts and Pitts, 2000;Nguyen et al, 2012;Xu et al, 2014). In this study, the nanomoles of organic hydroperoxides per microgram of SOA were quantified using the NPBA assay, represented by [OHP] m (nmol µg-SOA −1 ).…”
Section: Dtt Modulator: Non-catalytic Particulate Oxidizersmentioning
confidence: 99%